SULFIDE MINERALIZATION IN THE KROSNO ZONE FLISH ROCKS (NEW BESKYD TUNNEL AREA) - Guliy, V.; Kril, S.; Kovtun, O.; Kuzemko, Ya. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Results of the investigation of sulfide mineralization in flysch rocks within new Beskyd tunnel highway are presented. New tunnel goes through Oligocene massive gray sandstones with layers of dark siltstones and mudstones of the Krosno zone of the Ukrainian Carpathians. For the first time macro and microscopic morphogenetic features, composition of sulfides from the host rocks and late sulfide-quartz-carbonate veins and druses studies were carried out. Two main morphogenetic types of sulfides were defined. Earlier sulfides are represented by individual grain of cubic pyrite and it’s isometric and framboidal aggregates and rare grains of sphalerite in the host rocks. Formation of these sulfides is associated with formation of host sandstones and mudstones. The second type is connected with sulphide-quartz-carbonate veins and druses. It was formed during faults formation in already lithified rocks. Late sulfides formed mineral aggregates and individual cubic and cub-octaedr crystals of pyrite. Composition of pyrite from both morphogenetic types corresponds to pure FeS2.